A comparative evaluation of the time to frame removal for tibia fractures treated with hexapod and Ilizarov circular frames. Issue 3 (March 2023) - Watts, Arun; Sadekar, Vilas; Moulder, Elizabeth; Souroullas, Panayiotis; Hadland, Yvonne; Barron, Elizabeth; Muir, Ross; Sharma, Hemant
Abstract: Introduction: Traditional Ilizarov and hexapod frames have different biomechanical properties and there is limited literature regarding their effect on time to fracture union or time to frame removal. Methods: Tibial fractures managed with a circular frame at a tertiary limb reconstruction referral centre between 2011 and 2018 were retrospectively identified from a prospectively maintained database. They were classified into three treatment groups; Ilizarov style, Taylor Spatial Frame (TSF) and TrueLok Hex (TL-Hex). Data were extracted from electronic patient records and digital radiographs. The primary outcome was time to frame removal, which was seen as an indicator of clinical and radiological fracture union. Odds ratios were calculated with the clinical significance set at 30 days. Results: 274 patients (median age 49 years, 36% female) were included in the analysis. 8.4% Ilizarov, 10.5% TSF and 13.5% TL-Hex frames required further surgery to aid fracture healing ( p  = 0.38). 30% of patients had open fractures. Median time to removal for Ilizarov, TSF & TL Hex frames was 167, 198 and 185 days respectively. There was a significant difference between Ilizarov and hexapod frames. Both TSF (OR 2.2, p <0.003) and TL-Hex (OR 1.8, p <0.04) had a significantly increased time to removal of 30 days or more compared with Ilizarov frames.The time to frame removal in metaphyseal fractures was significantly shorter for Ilizarov frame fixation than hexapod frames ( p  = 0.04). Open fractures were significantly more likely to require at least 30 days extra time to removal than closed fractures (OR 3.3, p <0.001). There was no significant difference in the time to frame removal between fracture location, age or sex. Conclusion: Ilizarov frames have demonstrated a reduced time to frame removal in the management of tibial fractures than hexapod frames. Differences in the time to frame removal, an indicator of time to fracture union, may be due to the different mechanical properties of the frame, or early disruption of the fracture haematoma through secondary frame manipulation and fracture reduction, increased proportion of metaphyseal fractures treated with Ilizarov, or patient selection. The healing time was comparable across the tibia. Pooled meta-analyses may be able to further quantify these associations.